1995
DOI: 10.1006/dbio.1995.1210
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Spatially Specific Enhancer Element in the Chicken Msx-2 Gene That Regulates Its Expression in the Apical Ectodermal Ridge of the Developing Limb Buds of Transgenic Mice

Abstract: Msx-2 is a member of the Msx family of homeobox-containing genes expressed in a variety of embryonic tissues involved in epithelial-mesenchymal interactions and pattern formation. In the developing chick limb bud, Msx-2 is expressed in the apical ectodermal ridge, which plays a crucial role in directing the growth and patterning of limb mesoderm. In addition, Msx-2 is expressed in the anterior nonskeletal-forming mesoderm of the limb bud, in the posterior necrotic zone, and in the interdigital mesenchyme. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…Increased osteoblast cells and higher mineralized nodule formation explain the enhancement of proliferation by LIPUS (12,22,23). In addition, LIPUS affects on differentiation of osteoblast cells, which is shown by increased ALPase, and transcriptional factors, Runx2 (3,22,(24)(25)(26)(27)(28). Ultrasound stimulates PEG2 and COX-2 in osteoblast cells, and the expression of signals accelerates the bone regeneration in tissue engineering (1,11,(29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased osteoblast cells and higher mineralized nodule formation explain the enhancement of proliferation by LIPUS (12,22,23). In addition, LIPUS affects on differentiation of osteoblast cells, which is shown by increased ALPase, and transcriptional factors, Runx2 (3,22,(24)(25)(26)(27)(28). Ultrasound stimulates PEG2 and COX-2 in osteoblast cells, and the expression of signals accelerates the bone regeneration in tissue engineering (1,11,(29)(30)(31).…”
Section: Resultsmentioning
confidence: 99%
“…Dlx5 expression is related with osteoblast differentiation, and occurs in the final stages of osteoblast differentiation in vitro (26). Msx2 is predominantly expressed by proliferating osteoblasts and preosteoblasts, but its expression decreases according to terminal osteoblast differentiation (26)(27)(28).…”
Section: Differentiationmentioning
confidence: 99%
“…The homeobox proteins Dlx5 and Msx2 appear to regulate the development of mineralized tissues, including bone, cartilage, and dentin [26][27][28][29][30]. Dlx5 expression correlates with osteoblast differentiation and is at a maximum in the final stages of osteoblast differentiation in vitro when the extracellular matrix mineralizes, suggesting that Dlx5 may be involved in the differentiation of osteogenic cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…FGFs have been previously shown to regulate msx-1 and msx-2 expression (Sumoy et al, 1995;Wang and Sassoon, 1995), and on the basis of experimental evidence, it has been proposed that these genes participate in controlling cell proliferation and regeneration of digit tips in the developing mouse limb (Reginelli et al, 1995). However, the expression pattern in the limb and other embryo regions has suggested that these genes also participate in the process of cell death and that they are regulated by BMPs.…”
Section: Molecular Control Of Digit Growth and Interdigital Cell Deathmentioning
confidence: 99%